In Vitro Digestibilities of Plants Utilized by Barren-Ground Caribou - Thomas, Donald C.; Kroeger, Peter; Hervieux, David (ARCTIC, 1984)
Rumen fluids of barren-ground caribou (Rangifer tarandus groenlandicus) were used with standard in vitro procedures in March 1981 to investigate the relative digestibilities of forages collected on caribou winter ranges in the southern Northwest Territories. In vitro dry matter disappearance (IVDMD) of the three most abundant arboreal lichens, when fermented in test tubes for 60 h, averaged 67% compared with 43% for the seven most common terricolous lichens. The DMD of leaves of the most common shrubs, Vaccinium vitis-idaea, Empetrum nigrum, Arctostaphylos spp., and Ledum spp. averaged 46% (37-51%). Eight bryophyte species averaged 17% (7-28%) DMD. The DMD of species of three lichen genera with low protein contents, Cladina, Cladonia, and Cetraria, continued to increase with increasing fermentation periods up to 180 h. Nine species of lichens averaged 49% DMD when fermented for 60 h in test tubes, 64% when fermented in Erlenmeyer flasks, and 76% when 60 mg of urea was added to flasks. DMDs of 22 plant species were significantly higher in March 1981 than in similar tests conducted one year earlier. This annual variation in the digestive capacities of ruminal fluids was associated with the physical condition of the caribou and may have been related to their nutritional history.Key words: Canada, caribou, digestibilities, in vitro, lichens, nutrition, Rangifer Mots clés: Canada, caribou, digestibilité, in vitro, lichens, nutrition, Rangifer